Plight of the commons: 17 years of wildlife trafficking in Cambodia. (January 2020) - Heinrich, Sarah; Ross, Joshua V.; Gray, Thomas N.E.; Delean, Steven; Marx, Nick; Cassey, Phillip
Abstract: Southeast Asia is a hub for wildlife trafficking. Since 2001, the Wildlife Rapid Rescue Team (WRRT), a multi-agency law enforcement unit under the authority of the Cambodian Forestry Administration, has operated in Cambodia to counteract wildlife trafficking. We have analysed confiscation records from the WRRT for 2001–2018 to determine the compositional trends of trafficked species in Cambodia, and identify any detectable conservation gaps. Confiscations involved 95% native species. Over 60% of all confiscated species were either: (i) not listed in CITES; (ii) listed as Least Concern on the IUCN Red List; and/or (iii) Common under the Cambodian Forestry Law. These common, and usually less appreciated, species in trade may face greater future threats through trafficking and thus require better protection. Birds had the most number of animals confiscated, and songbirds were particularly heavily trafficked. In terms of the number of incidents, reptiles were the most confiscated Class. A small number of specific reptile species were consistently targeted, and particularly prominent was turtle and tortoise trafficking. Conversely, birds appeared to be trafficked opportunistically. Most bird species were only confiscated in a single year, and almost two thirds of all bird species were replaced by different species each year. We show that Cambodia is contributing substantially to the bird trade and this may be an under-reported element of the Asian songbird crisis.